2012
DOI: 10.1016/j.neuron.2012.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Simulate Others' Decisions

Abstract: A fundamental challenge in social cognition is how humans learn another person's values to predict their decision-making behavior. This form of learning is often assumed to require simulation of the other by direct recruitment of one's own valuation process to model the other's process. However, the cognitive and neural mechanism of simulation learning is not known. Using behavior, modeling, and fMRI, we show that simulation involves two learning signals in a hierarchical arrangement. A simulated-other's rewar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
206
5
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(233 citation statements)
references
References 58 publications
21
206
5
1
Order By: Relevance
“…Learning behavior in the self, prosocial, and no one conditions was modeled using a reinforcement learning (RL) algorithm (2), which has been extensively used to examine the behavioral and neural basis of arbitrary visuomotor associations in both self and social contexts (13,(17)(18)(19). The RL model assumes that the associative value of an action (or stimulus) changes when new information reveals that the actual outcome of a decision is different from the expected outcome (2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Learning behavior in the self, prosocial, and no one conditions was modeled using a reinforcement learning (RL) algorithm (2), which has been extensively used to examine the behavioral and neural basis of arbitrary visuomotor associations in both self and social contexts (13,(17)(18)(19). The RL model assumes that the associative value of an action (or stimulus) changes when new information reveals that the actual outcome of a decision is different from the expected outcome (2).…”
Section: Methodsmentioning
confidence: 99%
“…The ventral striatum, sgACC, dACC, and DLPFC are also implicated in processing information about rewards others will receive (12-16), PEs when interacting with others (13,(17)(18)(19), and prosocial behavior (e.g., refs. 4-7 for reviews).…”
mentioning
confidence: 99%
“…For instance, observing that others receive painful shocks following a visual stimulus can lead to conditioned fear responses and amygdala activation to this visual stimulus, even though participants never experienced the shocks themselves 71 . For positive values, several further studies also suggested that vicarious learning may follow computational principles that are similar to those for learning through personal experience [72][73][74][75] . For example, one recent study induced prediction errors at the outcome stage of altruistic choices by unexpectedly changing the outcome, either for the…”
Section: Vicarious Decision Makingmentioning
confidence: 99%
“…These studies thus suggest that both experience-based and vicarious learning of anticipated values have the same neural substrate (which supports the common currency schema). However, two other studies suggest that vicarious social learning also draws on distinct prediction-error computations in different neural structures 74,75 . These studies showed both vicarious reward prediction errors in the vmPFC (FIG.…”
Section: Prisoner's Dilemma Gamementioning
confidence: 99%
See 1 more Smart Citation